STRATEGI PENGEMBANGAN HIJAUAN UNTUK PENINGKATAN KETERSEDIAAN PAKAN TERNAK RUMINANSIA - Trisnadewi, Anak Agung Ayu Sri (Buletin Udayana Mengabdi; Vol 24 No 3 (2025): Buletin Udayana Mengabdi, 2024)
The problem that is often encountered in the development of ruminant livestock is the availability of abundant forage during the rainy season and a limited amount during the dry season. These strategies for developing forage need to be carried out so that the availability of feed is guaranteed and can meet the nutritional needs of livestock. The strategy for developing forage is through forage cultivation technology including land management, fertilization, planting methods, and development of superior types of grass and legumes. Community service activities w ere attended by 30 participants from among livestock breeders and were attended by the Head of Pengotan Village. Community service activities through counseling, discussions, and making demonstration plots for forage seeds. The types of grass developed are Panicum maximum grass and elephant grass. The types of grass developed are Panicum maximum grass and elephant kate grass ( Pennisetum purpureum cv. Mott) as well as the legumes Centrosema pubescens , Clitoria ternate a, and a protein source weed Asystasia gangetica . Planting forage using a monoculture system and mixed planting of grasses and legumes. From the results of the service carried out, it can be concluded as follows: 1) the service was attended by farmer breeders who were very enthusiastic about developing forage; 2) the service is carried out with 2 (two) activities, namely socialization and making forage development demonstration plots. The grass and legumes planted in the demonstration plot have grown and developed well